Marriage and immigrants in Cape Town: 1930–1970 - Rommelspacher, Amy F.; Fourie, Johan (Contree, 2025)
In colonial settler societies, a shortage of white marriageable women was often a concern, and until 1936, there were more white men that white women in Cape Town. The question of who marries who becomes particularly interesting in such contexts, especially in light of a constant stream of European immigrants to the city in the first half of the 20th-century. In our previous work, we discussed the merits of church marriage records as a source. Here we analyse marriage records from 1930 to 1970 and a household survey from 1938 to 1939 to gain insights into how immigrants acted in the marriage market in Cape Town during the period, with a focus on white inhabitants of the city in the context of a historical shortage of white women. Contribution: In this preliminary study, we find that most immigrants married other immigrants, and that if immigrant women married South African-born men, they married the wealthier men.